A review of available chargers for electric vehicles: United States of America, European Union, and Asia. (July 2019) - Knez, Matjaz; Zevnik, Gašper Kozelj; Obrecht, Matevz
Abstract: This research focuses on the incompatibility of chargers for electric vehicles between different vehicle brands and types. The basics of electric vehicles and their charging are presented. The three biggest electric vehicle markets (United States of America, European Union, and Asia) were studied to establish which electric vehicles and consequently what kind of chargers were sold between 2013 and 2015 and to examine the market share of existing chargers for all three studied markets. A short overview of various countries' policies for these markets is included as regards promoting and favouring electric vehicles and standardizing the chargers. This study has revealed that the most common charger in the USA is J1772, in the European Union Mennekes and in China GB/T. The number of J1772 and CHAdeMO chargers is decreasing rapidly, while Mennekes (which also has the highest share) and especially GB/T chargers are on the rise. China also made the most significant breakthrough in 2015 with GB/T as a leading charger type. Highlights: This six best selling electric vehicles in all studied markets (United States of America, Europe and Asia) have five different chargers. The most common charger in the United States of America is J1772, in the European Union Mennekes and in China GB/T. The number of J1772 and CHAdeMO chargers is decreasing rapidly, while Mennekes and especially GB/T chargers are on the rise. China made the most significant breakthrough in 2015 with the GB/T charger.